Australian Group on Antimicrobial Resistance (AGAR) Australian Enterococcal Surveillance Outcome Program (AESOP) Bloodstream Infection Annual Report 2024 - Coombs, Geoffrey; Daley, Denise; Form, Auriane; Li, Xing; Torres, Christian; Mowlaboccus, Shakeel (Communicable Diseases Intelligence, 2025)
From 1 January to 31 December 2024, fifty-five institutions across Australia participated in the Australian Enterococcal Surveillance Outcome Program (AESOP). The aim of AESOP 2024 was to determine the proportion of enterococcal bacteraemia isolates in Australia that were antimicrobial resistant, and to determine the molecular epidemiology of the reported Enterococcus faecium isolates. Of the 1,461 unique episodes of enterococcal bacteraemia investigated, 92.5% were caused by either E. faecalis (51.5%) or E. faecium (41.0%). Ampicillin and vancomycin resistance were not detected in E. faecalis but were detected in 96.8% and 44.5% of E. faecium respectively. Five linezolid-resistant E. faecalis isolates were identified, for which the linezolid minimum inhibitory concentrations (MICs) ranged from 6.0 mg/L to 8.0 mg/L. All five isolates harboured the linezolid resistance optrA gene and were vancomycin susceptible. One linezolid-resistant E. faecium was confirmed with an MIC of 6.0 mg/L. The isolate was vancomycin and teicoplanin resistant and harboured vanA and optrA genes. Overall, 49.8% of E. faecium isolates harboured the vanA and/or the vanB gene: within these isolates, 40.2% harboured vanA, 58.8% harboured vanB, and 1.0% harboured vanA and vanB. The percentage of vancomycin-resistant E. faecium bacteraemia isolates in Australia remains substantially higher than that recorded in most European countries. The E. faecium isolates consisted of 56 multi-locus sequence types (STs); 85.7% of isolates were classified into eight STs, each containing ten or more isolates. The eight STs (ST17, ST78, ST80, ST117, ST555, ST796, ST1421 and ST1424) belonged to clonal complex (CC) 17, a global hospital-adapted polyclonal E. faecium CC, and were found in most Australian jurisdictions. Overall, 54.6% of E. faecium isolates belonging to the eight predominant STs harboured the vanA or vanB gene. AESOP 2024 has shown that enterococcal bacteraemia episodes in Australia continue to be frequently caused by polyclonal ampicillin-resistant high-level gentamicin-resistant vanA- or vanB-positive E. faecium which have limited treatment options.